The epidemiology of substance use among street children in resource‐constrained settings: a systematic review and meta‐analysis. (12th July 2013) - Embleton, Lonnie; Mwangi, Ann; Vreeman, Rachel; Ayuku, David; Braitstein, Paula
Abstract: Aims: To compile and analyze critically the literature published on street children and substance use in resource‐constrained settings. Methods: We searched the literature systematically and used meta‐analytical procedures to synthesize literature that met the review's inclusion criteria. Pooled‐prevalence estimates and 95% confidence intervals (CI) were calculated using the random‐effects model for life‐time substance use by geographical region as well as by type of substance used. Results: Fifty studies from 22 countries were included into the review. Meta‐analysis of combined life‐time substance use from 27 studies yielded an overall drug use pooled‐prevalence estimate of 60% (95% CI = 51–69%). Studies from 14 countries contributed to an overall pooled prevalence for street children's reported inhalant use of 47% (95% CI = 36–58%). This review reveals significant gaps in the literature, including a dearth of data on physical and mental health outcomes, HIV and mortality in association with street children's substance use. Conclusions: Street children from resource‐constrained settings reported high life‐time substance use. Inhalants are the predominant substances used, followed by tobacco, alcohol and marijuana.